Transcriptome sequencing identifies a noncoding, deep intronic variant in CLCN7 causing autosomal recessive osteopetrosis - Odelia Chorin; Naomi Yachelevich; Khaled Mohamed; Ilana Moscatelli; John Pappas; Kim Henriksen; Gilad D. Evrony (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Over half of children with rare genetic diseases remain undiagnosed despite maximal clinical evaluation and DNA‐based genetic testing. As part of an Undiagnosed Diseases Program applying transcriptome (RNA) sequencing to identify the causes of these unsolved cases, we studied a child with severe infantile osteopetrosis leading to cranial nerve palsies, bone deformities, and bone marrow failure, for whom whole‐genome sequencing was nondiagnostic. Methods We performed transcriptome (RNA) sequencing of whole blood followed by analysis of aberrant transcript isoforms and osteoclast functional studies. Results We identified a pathogenic deep intronic variant in CLCN7 creating an unexpected, frameshifting pseudoexon causing complete loss of function. Functional studies, including osteoclastogenesis and bone resorption assays, confirmed normal osteoclast differentiation but loss of osteoclast function. Conclusion This is the first report of a pathogenic deep intronic variant in CLCN7, and our approach provides a model for systematic identification of noncoding variants causing osteopetrosis—a disease for which molecular‐genetic diagnosis can be pivotal for potentially curative hematopoietic stem cell transplantation. Our work illustrates that cryptic splice variants may elude DNA‐only sequencing and supports broad first‐line use of transcriptome sequencing for children with undiagnosed diseases.